Rural Development Programme: phase III (1993-1995), appraisal, volume I, main report - BRAC (© BRAC, 2016)
1. Introduction 2. Summary of main recommendations 3. Background and context 4. Overview and commentary on the proposed expansion 5. Key issues and challenges for future growth 6. Institutional development at the local level 7. Sectoral programmes 8. Credit services 9. Training 10. Planning, management and organisational development